Fortified Iodine Milk Improves Iodine Status and Cognitive Abilities in Schoolchildren Aged 7–9 Years Living in a Rural Mountainous Area of Morocco - Fatima Ezzahra Zahrou; Mehdi Azlaf; Imane El Menchawy; Mohamed El Mzibri; Khalid El Kari; Asmaa El Hamdouchi; Fatima-Zahra Mouzouni; Amina Barkat; Hassan Aguenaou (Journal of Nutrition and Metabolism)
Iodine is required for the production of the thyroid hormones essential for the growth and development of the brain. All forms of iodine deficiency (ID) affect the mental development of the child. Our study aims to assess the impact of ID on the intellectual development of Moroccan schoolchildren and to evaluate the effect of consumption of fortified milk on reducing ID. In a double-blind controlled trial conducted on schoolchildren, children were divided into two groups to receive fortified milk (30% of cover of RDI iodine) or nonfortified milk for 9 months. Urinary iodine was analyzed using the Sandell-Kolthoff reaction, a dynamic cognitive test using Raven’s Standard Progressive Matrices to assess learning potential was performed at baseline and end line, and anthropometric assessment was done only at baseline. The study included schoolchildren who were severely iodine deficient. The prevalence of malnutrition was high in both groups; in this study, we found improvements in iodine status and in cognitive abilities among Moroccan schoolchildren. Our study showed that the consumption of fortified milk led to a clear improvement in iodine status and also appeared to have a favorable effect on the cognitive ability of Moroccan schoolchildren in a rural mountainous region.